Distinction between Infection and Rejection in Lung Transplantation. Issue 5805 (8th April 1972) - Cullum, P. A.; Bewick, M.; Shilkin, Keith; Tee, D. E. H.; Ayliffe, P.; Hutchison, D. C. S.; Laws, J. W.; Mason, S. A.; Reid, Lynne; Hugh-Jones, P.; Macarthur, A. M.
Abstract : In distinguishing between infection and rejection after human lung transplantation clinical and radiological features were unhelpful, and even confusing. However, incipient rejection could be predicted and distinguished from infection by monitoring alterations in lymphocyte activity by the rosette inhibition test. Earlier prediction seems possible by detecting circulating lung-binding antibody. The ability to detect changes in the immunological status of a patient, even before clinical deterioration, has fundamental implications for the management of patients after transplantation.